2017
DOI: 10.1002/aelm.201700181
|View full text |Cite
|
Sign up to set email alerts
|

Morphology–Function Relationship of Thermoelectric Nanocomposite Films from PEDOT:PSS with Silicon Nanoparticles

Abstract: The relation of the thermoelectric figure of merit and the nanocomposite morphology is studied for thermoelectric thin films consisting of poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) with different amounts of silicon nanoparticles (Si‐NPs). An increase in the figure of merit of up to 150% is found for an Si‐NP concentration of 0.5 wt% as compared to pristine PEDOT:PSS films. The improvement originates from a disruption in the molecular ordering and therefore reduced electrical conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 72 publications
3
42
0
Order By: Relevance
“…This estimate is relatively reasonable, On the one hand, this work of material and the polymerization method are in good accordance with literature, and the thermal conductivity is not dependent on the oxidation state . On the other hand, the thermal conductivity of CPs is difficult to measure accurately, and the values are often only estimated in the literature . Therefore, using the optimum measured PF and the above κ // values, a maximum of ZT = 0.036 at 295 K was obtained.…”
Section: Resultssupporting
confidence: 78%
“…This estimate is relatively reasonable, On the one hand, this work of material and the polymerization method are in good accordance with literature, and the thermal conductivity is not dependent on the oxidation state . On the other hand, the thermal conductivity of CPs is difficult to measure accurately, and the values are often only estimated in the literature . Therefore, using the optimum measured PF and the above κ // values, a maximum of ZT = 0.036 at 295 K was obtained.…”
Section: Resultssupporting
confidence: 78%
“…15 Recently, Saxena et al showed that an improvement of thermoelectric properties of PEDOT:PSS can be achieved by the introduction of silicon nanoparticles that simultaneously affect conductivity, thermopower and thermal conductivity. 16 Lu et al…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been much progress in exible and stretchable electronic devices using organic semiconductors, ultra-thin silicon membranes, metal-based lms, serpentine lines or liquid metals, carbon nanotubes, silver nanowires, and intrinsically conductive polymers. [12][13][14][15][16] While these materials and structures provide excellent stretchability, devices fabricated from these materials are typically realized by lithographic or spin or spray coating techniques; the structurefabrication processes are complex and either expensive or incompatible with large-scale fabrication. 17,18 On the other hand, as the ultimate wearable platform, textile-based electronics have the proven advantages of their intrinsic properties, such as light weight, accessibility, comfort, breathability, and stretchability.…”
Section: Introductionmentioning
confidence: 99%